Comparison of childhood household injuries and risk factors between urban and rural communities in Ghana: A cluster-randomized, population-based, survey to inform injury prevention research and programming. Issue 7 (July 2021) - Stewart, Barclay; Gyedu, Adam; Otupiri, Easmon; Nakua, Emmanuel; Boakye, Godfred; Mehta, Kajal; Donkor, Peter; Mock, Charles
Highlights: The incidence of childhood household injuries in urban and rural Ghana was 594 and 542 injuries per 1, 000 child-years, respectively, which is ten times greater than the incidence among children in high-income countries. Urban children were more commonly injured by falling but less commonly injured by flame/hot substances, violence, or motor vehicles compared to rural children, offering differential opportunities for prevention. Based on the findings, several interventions could be effective, including: community-based, multi-strategy initiatives (e.g., home hazard reduction, provision of safety equipment, establishing community creches); traffic calming interventions in rural community clusters; and passive injury surveillance systems that collect data to inform violence and broader prevention strategies. Abstract: Background: Childhood household injuries incur a major proportion of the global disease burden, particularly in low- and middle-income countries (LMICs). However, household injury hazards are differentially distributed across developed environments. Therefore, we aimed to compare incidence of childhood household injuries and prevalence of risk factors between communities in urban and rural Ghana to inform prevention initiatives. Methods: Data from urban and a rural cluster-randomized, population-based surveys of caregivers of children <5 years in Ghana were combined. In both studies, caregivers were interviewed about childhood injuries that occurred within the past 6 months and 200 meters of the home that resulted in missed school/work, hospitalization, and/or death. Sampling weights were applied, injuries and incidence rate ratios (IRRs) were described, and multi-level regression was used to identify and compare risk factors. Results: We sampled 200 urban and 357 rural households that represented 20, 575 children in Asawase and 14, 032 children in Amakom, Ghana, respectively. There were 143 and 351 injuries in our urban and rural samples, which equated to 594 and 542 injuries per 1, 000 child-years, respectively (IRR 1.09, 95%CI 1.05-1.14). Toddler-aged children had the highest odds of injury both urban and rural communities (OR 3.77 vs 3.17, 95%CI 1.34-10.55 vs 1.86-5.42 compared to infants, respectively). Urban children were more commonly injured by falling (IRR 1.50, 95%CI 1.41-1.60), but less commonly injured by flame/hot substances (IRR 0.51, 95%CI 0.44-0.59), violence (IRR 0.41, 95%CI 0.36-0.48), or motor vehicle (IRR 0.50, 95%CI 0.39-0.63). Rural households that cooked outside of the home (OR 0.36, 95%CI 0.22-0.60) and that also supervised older children (OR 0.33, 95%CI 0.17-0.62) had lower odds of childhood injuries than those that did not. Conclusions: Childhood injuries were similarly common in both urban and rural Ghana, but with different patterns of mechanisms and risk factors that must be taken into account when planning prevention strategies. However, the data suggest that several interventions could be effective, including: community-based, multi-strategy initiatives (e.g., home hazard reduction, provision of safety equipment, establishing community creches); traffic calming interventions in rural community clusters; and passive injury surveillance systems that collect data to inform violence and broader prevention strategies.